PJMHS 2021
DOI: 10.53350/pjmhs211551441
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of COVID-19 among dental practitioners of Multan

Abstract: Background: Corona Virus Disease 2019 (COVID-19) is a global pandemic still at large whose vaccination is in a trial phase. Dental practitioners are at high risk of exposure to this deadly epidemic. Therefore, the purpose of this study is to assess the knowledge and practice of dentists in the city of Multan, Pakistan. Method: This cross-sectional study was carried out in Multan, Pakistan from January to March 2021. A 30 items valid and reliable self-administrative questionnaire was used to assess the knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…40 GAD-7 was the most commonly used measure (seven studies). 41,42,43,44,45,46,47 Categorisation of the specific MHOs for dentists (listed in Table 1) confirmed the reporting of symptoms of anxiety in 40 studies, including Chen et al; 43 fear in 44 studies; 48,49 depression in 12 studies; 50 psychological distress in 13 studies; 51 burnout in 5 studies; 52 and work-related stress in 22 studies. 53 Ahmed et al 54 confirmed symptoms of anxiety in 78% of their reporting dentists, highlighting the fear of infection and transmission to families.…”
Section: Resultsmentioning
confidence: 63%
“…40 GAD-7 was the most commonly used measure (seven studies). 41,42,43,44,45,46,47 Categorisation of the specific MHOs for dentists (listed in Table 1) confirmed the reporting of symptoms of anxiety in 40 studies, including Chen et al; 43 fear in 44 studies; 48,49 depression in 12 studies; 50 psychological distress in 13 studies; 51 burnout in 5 studies; 52 and work-related stress in 22 studies. 53 Ahmed et al 54 confirmed symptoms of anxiety in 78% of their reporting dentists, highlighting the fear of infection and transmission to families.…”
Section: Resultsmentioning
confidence: 63%